MORTGAGE RIGHTS INPUT ASSISTANCE ON MITRA ATR BPN SYSTEM IN KANTOR NOTARIS DAN PPAT RIAN SUGITO S.H., M.KN - Wini Rosalya; Abdurrakhman Alhakim (ConCEPt - Conference on Community Engagement Project, 2022)
Mortgage right is a guaranteed right over property where assets are seen as a unity towards the property that is utilized by the creditor to acquire collateral rights for debt payments. Mortgage rights are regulated in Indonesia under Peraturan Menteri Agraria Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 9 Tahun 2019 tentang Pelayanan Hak Tanggungan Terintegrasi secara elektronik. Input of Mortgage via online system of Mitra ATR BPN improves the simplicity indicator in public service for the people in utilizing communication and information by applying electronic based land services. Land deeds officials and banks are parties who are involved in the execution of mortgage rights applications. The parties need to have a proper comprehension on the technical and be more thorough in order to minimize error in the input of mortgage rights within the electronic system. Currently, the registration of mortgage rights are done through an online application of mitra.atrbpn.go.id by a registered user as land deeds officials and financial service officers in order to process the mortgage certificate legalized by the National Land Agency